Development of a pocketbook for the prevention of bullying in school - Sarah Kartini Izach; Nur Wahyu Rochmadi; Edi Suhartono (Inovasi Kurikulum, 2024)
The phenomenon of bullying in schools is often overlooked despite its significant negative impacts on victims, such as low self-esteem and risk of depression. This study aims to develop a pocketbook as a bullying prevention medium at SMA Muhammadiyah 10 Surabaya. Using the ADDIE model, the study involves five stages: analysis, design, development, implementation, and evaluation. The school's need for bullying prevention materials was identified in the analysis stage. The pocketbook design was developed using Canva, encompassing relevant and engaging content. The pocketbook was then implemented through socialization in the school. Evaluation was conducted through expert validation and feedback from teachers and students. Validation results indicated that the pocketbook is highly rated and suitable for use. Feedback from teachers and students showed very high scores, indicating that the pocketbook effectively enhances understanding of the importance of preventing bullying behavior. The pocketbook uses colored images and structured content to enhance student engagement and comprehension. With this pocketbook, a safe and comfortable learning environment is hoped to be created, fostering a culture of mutual respect in schools. The pocketbook can serve as a tool in socialization and strengthening material on bullying prevention in schools.